Limits to modern contraceptive use among young women in developing countries: a systematic review of qualitative research - Wight Daniel; Petticrew Mark; Parkes Alison; Williamson Lisa M; Hart Graham J (BMC, 2009)
Abstract Background Improving the reproductive health of young women in developing countries requires access to safe and effective methods of fertility control, but most rely on traditional rather than modern contraceptives such as condoms or oral/injectable hormonal methods. We conducted a systematic review of qualitative research to examine the limits to modern contraceptive use identified by young women in developing countries. Focusing on qualitative research allows the assessment of complex processes often missed in quantitative analyses. Methods Literature searches of 23 databases, including Medline, Embase and POPLINE®, were conducted. Literature from 1970-2006 concerning the 11-24 years age group was included. Studies were critically appraised and meta-ethnography was used to synthesise the data. Results Of the 12 studies which met the inclusion criteria, seven met the quality criteria and are included in the synthesis (six from sub-Saharan Africa; one from South-East Asia). Sample sizes ranged from 16 to 149 young women (age range 13-19 years). Four of the studies were urban based, one was rural, one semi-rural, and one mixed (predominantly rural). Use of hormonal methods was limited by lack of knowledge, obstacles to access and concern over side effects, especially fear of infertility. Although often more accessible, and sometimes more attractive than hormonal methods, condom use was limited by association with disease and promiscuity, together with greater male control. As a result young women often relied on traditional methods or abortion. Although the review was limited to five countries and conditions are not homogenous for all young women in all developing countries, the overarching themes were common across different settings and contexts, supporting the potential transferability of interventions to improve reproductive health. Conclusion Increasing modern contraceptive method use requires community-wide, multifaceted interventions and the combined provision of information, life skills, support and access to youth-friendly services. Interventions should aim to counter negative perceptions of modern contraceptive methods and the dual role of condoms for contraception and STI prevention should be exploited, despite the challenges involved.